Molecular Determinants of the Estrogen Receptor-Coactivator Interface - Mak, Ho Yi (American Society for Microbiology, 1999)
Transcriptional activation by the estrogen receptor is mediated through its interaction with coactivator proteins upon ligand binding. By systematic mutagenesis, we have identified a group of conserved hydrophobic residues in the ligand binding domain that are required for binding the p160 family of coactivators. Together with helix 12 and lysine 366 at the C-terminal end of helix 3, they form a hydrophobic groove that accommodates an LXXLL motif, which is essential for mediating coactivator binding to the receptor. Furthermore, we demonstrated that the high-affinity binding of motif 2, conserved in the p160 family, is due to the presence of three basic residues N terminal to the core LXXLL motif. The recruitment of p160 coactivators to the estrogen receptor is therefore likely to depend not only on the LXXLL motif making hydrophobic interactions with the docking surface on the receptor, but also on adjacent basic residues, which may be involved in the recognition of charged residues on the receptor to allow the initial docking of the motif.